PERBANDINGAN LEMAK, PROTEIN, LAKTOSA DAN pH SUSU SAPI FRIESIAN HOLSTEIN PADA PEMERAHAN PAGI DAN SORE DI CV BEN BUANA SEJAHTERA SUMEDANG - Raden Febrianto Christi; Ajat Sudrajat; Nilawati Widjaja; Endah Yuniarti (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2022)
The chemical components of milk greatly determine the quality of milk produced from an animal. The purpose of this study was to determine the ratio of fat, protein, lactose and pH at morning and evening milking at CV Ben Buana Sejahtera (BBS Farm) Jatinangor District, Sumedang Regency. The research method used was paired t test with milk samples from 18 dairy cows with different lactation periods. 100 ml of milk samples were taken from each cow with different milking times, morning and evening, then put in a coolbox to test the chemical components of milk. in the Laboratory. The results showed that the average levels of fat, protein and lactose in milk in the morning were higher (P<0.05) than in the afternoon but the pH values ​​showed the same results. The conclusion shows that the comparison of the chemical quality of cow's milk in the morning and evening milking at CV BBS Farm gives a difference in the value of fat, protein, lactose content but does not affect the pH value and the nutritional components are still in normal conditions.